Assessing food safety knowledge, attitude and practices (KAP) among food handlers in Universiti Teknologi Mara, Shah Alam / Maria Mohd Salleh - Mohd Salleh, Maria (2013)
Food handlers’ plays a major role in preventing outbreaks of foodborne illness. The purpose of this study were to assess the knowledge attitude and practice (KAP) on food safety among food handlers in Universiti Teknologi MARA (UiTM), Shah Alam. The convenience sample of 112 food handlers was collected from 62 food premises (restaurants, kiosk, cafeteria and food court) in UiTM, Shah Alam. Descriptive statistic were used to analyse the data regarding food handlers’ knowledge related to food safety area (personal hygiene, foodborne illness, cross contamination, time and temperature control and sanitizing), attitude and practices. In general the respondent overall knowledge was satisfactory with a mean score knowledge of 3.96. Majority of the food handlers reported positive attitudes on most aspects such as the responsibility to obtain food safety and to ensure that food is save to serve. The attitude significantly contributed to food safety practice findings in this study. The high value of (r = 0.978, p ≤ 0.00) clearly indicates that attitude strongly determine food handlers’ actual practices in their working food premises. This shows that, the lack of knowledge in food safety will not influence their attitude and practices thus foodborne illness can be avoided. Monitoring and identifying food handler’s level of knowledge, attitude and practices (KAP) is important to assure food safety in food premises operations therefore, prevent the occurrence of foodborne illnesses, a health public problem in UiTM and Malaysia. This study which is having huge impact nationally should be done as a national initiative with collaboration from relevant government agencies such as the Ministry of Health or other related agencies to give exposure to food safety among food handlers’ in UiTM. The researcher also hopes the gap in this paper will be studied by other researchers in the future.